A Response Of Giving Rice Husk Charcoal And Goat Dung On Growth And Production Of Corn Plants (Zea Mays L.) - Yudi Satrio Adiwibowo; Sulardi, Sulardi; M. Wasito (Jurnal Scientia, 2024)
This study aims to determine the response of rice husk charcoal and goat manure solid organic fertilizer to the growth and production of corn (Zea mays). This study used a Factorial Randomized Block Design (RAK) with 2 treatment factors and 3 blocks. The first factor is rice husk charcoal with each dose of A0 = 0 kg/plot, A1 = 1 kg/plot and A2 = 2 kg/plot. The second factor is the provision of goat manure solid organic fertilizer with each dose of K0 = 0 kg/plot, K1 = 1 kg/plot, K2 = 2 kg/plot and K3 = 3 kg/plot. Observation data were analyzed using analysis of variance and continued with the Duncant test. The parameters observed were plant height, stem diameter, number of cobs per sample, number of cobs per block, cob weight per sample and cob weight per block. The results of the study showed that the provision of rice husk charcoal and solid organic fertilizer of goat manure had a very significant effect on plant height, stem diameter, number of cobs per sample, number of cobs per block, weight of cobs per sample and weight of cobs per block. In the interaction of the combination of treatments between the provision of rice husk charcoal and solid organic fertilizer of goat manure did not have a significant effect on all parameters observed.